Indonesian Context of Health Paradiplomacy: A Bibliography - Siti Fitrah Ramadania; Moh. Syafarudin A.L Gula; Siti Febrianty Mohammad; Moh Ryan YL Saad (Universitas Bina Mandiri Gorontalo, 2025)
2020-2024, examining the role of sub-national actors in national health diplomacy agenda. Health issues have transformed from domestic affairs into diplomatic instruments, enabling local governments, hospitals, and universities to strengthen health capacity through international networks without complete dependence on central government.Using qualitative descriptive approach and content analysis of five selected news articles, this research identifies patterns of international cooperation by local actors during 2022-2025. Analysis results show the main focus is collaboration and services to improve regional health service quality to international standards and promote health independence.Forms of paradiplomacy include human resource exchange, research, and medical infrastructure strengthening, such as East Java Province's cooperation with LUMC Netherlands for world-class hospitals, and Bandung City's partnership with Hamamatsu Japan involving industrial and educational sectors. Local actors such as governors, secretaries, city governments, and universities play crucial and equal roles in driving these initiatives.This documentation is expected to serve as academic reference and evaluation basis for developing sustainable international health cooperation strategies in Indonesia.